2016
DOI: 10.1007/s00249-016-1128-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the regulatory light chain of myosin in striated muscle: methodological perspectives

Abstract: Phosphorylation of the regulatory light chain (RLC) of myosin modulates cellular functions such as muscle contraction, mitosis, and cytokinesis. Phosphorylation defects are implicated in a number of diseases. Here we focus on striated muscle where changes in RLC phosphorylation relate to diseases such as hypertrophic cardiomyopathy and muscular dystrophy, or age-related changes. RLC phosphorylation in smooth muscle and non-muscle cells are covered briefly where relevant. There is much scientific interest in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 204 publications
(285 reference statements)
0
40
0
Order By: Relevance
“…Myosin molecules are tightly associated with different myosin light chains, modulating the stability of the myosin head, contributing to force production, and altering the association with the actomyosin network [45,46]. The regulatory isoforms MYL2 and MLC2F are phosphorylated at S14 and S15, and these modifications are associated with force potentiation in fast skeletal muscles [47,48].…”
Section: Phosphoproteomics Reveals Distinct Kinase Activities Betweenmentioning
confidence: 99%
“…Myosin molecules are tightly associated with different myosin light chains, modulating the stability of the myosin head, contributing to force production, and altering the association with the actomyosin network [45,46]. The regulatory isoforms MYL2 and MLC2F are phosphorylated at S14 and S15, and these modifications are associated with force potentiation in fast skeletal muscles [47,48].…”
Section: Phosphoproteomics Reveals Distinct Kinase Activities Betweenmentioning
confidence: 99%
“…Activation of the muscle not only involves the canonical movement of tropomyosin on the thin filament to expose binding sites for myosin heads but also additionally requires myosin heads to be released from their shutdown state (Irving 2017 ). It is likely that phosphorylation of the regulatory light chains (RLCs) plays a role in this in both cardiac and skeletal muscles (Yu et al 2016 ), through affecting the stability of the shutdown state.…”
Section: Myosin Structure—a Brief Overviewmentioning
confidence: 99%
“…The effects of phosphorylation of RLC MYL2 at Ser15 by the cardiac and skeletal myosin light chain kinases (MLCK) have been extensively examined (89, 126, 624). Accordingly, it was demonstrated that it renders the lever arm of MyHC stiffer, potentiates isometric and concentric force production, and increases myofilament Ca 2+ sensitivity in both cardiac and skeletal muscles, reviewed in (514, 573, 574, 618). Consistent with these findings, constitutive expression of phosphomimetic Myl2 (i.e., Ser15Asp) in myocardia prevented the development of HCM in transgenic mice carrying the HCM-linked Asp166Val MYL2 missense mutation (620).…”
Section: Myosinmentioning
confidence: 99%